On Andropov‘s Question: Communism as a Problem of Comparative Historical Sociological Analysis (I) - Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 2007)
The article discusses the problem of the macrosociological classification of the communist societies, called „Andropov’s question“ alluding to the complaint of the Soviet leader (and the head of KGB for some 15 years) that he doesn’t know society under his rule. Pretheoretically, „communist societies“ can be identified as „societies shaped by the attempt to realize the Karl Marx utopian idea of society without classes and alienation“. „Andropov‘s question“ surfaces after one rejects the ideological self-descriptions of these societies as „socialist“. Author draws distinction between two strategies to face this question: the emic and the etic one. Emic perspective is represented by the critical Marxist analysis of the communist societies, classifying them as „degenerated worker’s state“, „deformed socialism“ or „state capitalist“ societies. Etic perspective is represented by non-Marxist theories of communism. The author proposes to classify them depending on the strategy of comparison used for concept formation and explanation. In the theories of communism as totalitarianism, communism is described as a pathology of modernity. This kind of analysis emphasizes the uniqueness of communism, with Nazist Germany as sole comparable case. The theories of communism as one of the many ways leading to modernity highlight its features shared with „normal“ modern societies and consider communism as an incomplete modernity. Theories of communist neotraditionalism (to be discussed in the sequel to this paper) use the social reality of traditional societies or those from the „third world“ where modernization has failed as communism’s mirror.